PARTICIPATORY ACTION RESEARCH: PENINGKATAN KESADARAN MASYARAKAT UNTUK MENJADIKAN LINGKUNGAN YANG BEBAS NARKOBA (Studi Kasus di Kompleks Permata, Jakarta Barat) - Ivo Noviana (Puslitbangkesos Kementerian Sosial RI, 2010)
Repressive and the eradication of drug abuse that had been conducted by law enforcement authorities in Kompleks Permata ineffective because it does not have the support of local community. Collectively inÂ community even against and denied the presence of law enforcement who want to take actions against the perpetrators of sellers and drug dealers in their area. Learning from the experience of handling similar cases in other countries, the government realized that to make changes to the region and free from drug abuse in Kompleks Permata's communittJ requires more than merely repressive approach and repressive measures.Â Awareness of local community to participated in making these changes. In order to support increased community awareness, the approach used ParticipatonJ Action Research (PAR) that a role and be useful toÂ support increased research on the environmental sensitivity of the public who live with the drug.